Complying with privacy legislation - Ataei, Mehrnaz (2018)
Ataei, M., Degbelo, A., Kray, C., & Santos, V. (2018). Complying with privacy legislation: from legal text to implementation of privacy-aware location-based services. ISPRS International Journal of Geo-Information, 7(11), [442]. DOI: 10.3390/ijgi7110442